Future images of employment in Japan : How Japanese youth perceives the future - Rahunen, Maria (My University, 2019)
This thesis aims to understand future of employment in Japan. The research question that guides this research asks what kind of concerns and expectations young Japanese people have of their future relating to employment. Japanese youth of today was chosen as the focus group, since they will be the ones working in the future and shaping the possible futures. The timeframe for future has been set as 2040. As Japan is an aging society, there is currently a shortage of workers, which has created societal challenges. The aim of this research was to examine if the Japanese youth of today has different values than their parents’ generation and explore what kind of alternative futures might become reality by the time they are their parents’ age. This has been done by first looking into the current characteristics of Japanese employment and the areas with most challenges as of now. The fieldwork for this research was conducted while I was studying as an exchange student in Japan. For four months, I took part on a course on futures consciousness and acted as a teaching assistant. The empirical data has been collected by compiling the class assignments and conducting personal discussions with students. To supplement the data, I have written down my own observations made while in Japan. To make sense of the gathered data, I have utilized the causal layered analysis as a tool. The four different levels of the causal layered analysis provide a platform for categorizing and presenting the data. The end products of the causal layered analysis are the images of future presented in this thesis. Based on the data analysis, I found four different alternative futures. The images represent four different alternative futures, which reflect the insights and forecasts of the Japanese students. The first of the images can be seen as the most desirable one in the students’ opinion, since it is the one that allows them to realize their dreams and goals. The same image is also in line with the official future image of Japan introduced by the Japanese government. In this image, intelligent technologies have provided a solution for most challenges. In the second image, immigration has provided a solution to the labor shortage. Importance of nature and neglection of technology are highlighted in the third image, while the fourth depicts Japan as a dying nation where challenges keep on increasing. Necessarily none of these images will become one hundred percent true in the future, but they provide an interesting look into the concerns, challenges and opportunities of the Japanese youth of today regarding their future. The findings show that there is a hope, that many aspects of employment will change in the future. The Japanese youth does not seem to place their career ahead of everything, which traditionally has been the norm especially for the men. The youth seems to have a strong belief in their personal futures and is focused on realizing their goals. On the other hand, there seems to be uncertainty when it comes to the future of Japan as a country. The views on their nation appear more negative when future is concerned.
Keywords: images of future, Japan, future of work, alternative futures, demographic shift, aging society, artificial intelligence, robotics, causal layered analysis